(Penelitian Kualitatif di Desa Tirem Kecamatan Lebak Wangi Kabupaten Serang Banten) - Elen Anne; Luluk Asmawati; Fahmi Fahmi (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
The aims of the research was to knowing parenting pattern of single parent 4-5 years age in the village of Tirem Lebak Wangi District Serang Banten regency, to know the process of parenting single parent with the ability to speak 4-5 years age children in the Village District Tirem Lebak Wangi Serang Banten. The research site is Desa Tirem. The research location was Tirem Village, Lebak Wangi Subdistrict, Serang Banten Regency. The research time was on May 1, 2018-May 30, 2018. The research method is qualitative method with phenomenology approach. The results of the research findings are a form of parenting of single parents 4-5 years age in Tirem Village, Lebak Wangi Subdistrict, Serang Banten District, authoritarian parenting and permissive parenting, The process of parenting single parent with the ability to speak 4-5 years age children in the Village District Tirem Lebak Wangi Serang Banten seen from through habituation bathing children in the bathroom, mother asked the colors that are around the child to the child and there are who can answer correctly and some who do not, mother feeding children, the mother asks the child about the feeling and there are children who can answer correctly and those who do not, mother asks about the forms around the child and no child can answer, the mother asks the sex and age to the child and there are children who can answer correctly and those who do not, the mother asks the child to repeat the story and no child can recount the story, and stimulation given by single parents to different children. The conclusion of the research results is that there is a relationship between parenting parents with the ability to speak children aged 4-5 years in Tirem Village, Lebak Wangi District, Serang Banten Regency. Specifically, it can be concluded (1) Parenting pattern applied by single parent of 4-5 years age child in Tirem Village Lebak Wangi Sub-district of Serang Banten Regency that is authoritarian parenting and permissive parenting pattern. (2) The ability to speak 4-5 years age children in the village of Tirem Lebak Wangi District Serang Banten regency is lower than the stage of development of children’s speech, especially the language aspect.